Entrepreneurial Education for Persons With Disabilities—A Social Innovation Approach for Inclusive Ecosystems - Krüger, Daniel; David, Alexandra (Frontiers in Education, 2020)
Fostering entrepreneurship and inclusive societies are on top of EU policy agenda. This article is bringing together both aims by discussing a social innovation framework for inclusive entrepreneurial education for persons with disabilities based on a co-creation and co-production approach. Similar to other disadvantaged groups, persons with disabilities can benefit from entrepreneurial skills for self-management or, on a next level, for starting own, opportunity-driven businesses. The framework is taking several building blocks into account considered necessary for successful entrepreneurial education for the beneficiaries. First, it is approaching the framework through a social innovation perspective. By this, it is suggesting a social innovation ecosystem perspective for discussing all relevant stakeholders and contextual aspects relevant for the framework. Second, it is suggesting to build on socially innovative, hence novel, practices by starting from co-creation and co-production in order to meet individual demands and needs of learners. It is furthermore taking the concept of universal design into account as it holds major implications for inclusive entrepreneurial education for persons with disabilities and is underlining the need of different, more suitable practices in entrepreneurship education and beyond, towards an inclusive learning ecosystem.